Geometric morphometric characteristics of Apis mellifera honeybee in Kazakhstan - ULZHAN NURALIEVA; KADYRBAI TAJIYEV; ZHANAR SHERALIEVA; MAXAT TOISHIMANOV; GAUKHAR MOLDAKHMETOVA; KAMSHAT TEMIRBAYEVA; AIGUL TAJIEVA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nuralieva U, Tajiyev K, Sheralieva Z, Toishimanov M, Moldakhmetova G, Temirbayeva K, Tajieva A. 2023. Geometric morphometric characteristics of Apis mellifera honeybee in Kazakhstan. Biodiversitas 24: 4402-4409. This study was conducted in the whole beekeeping region of Kazakhstan. We researched morphological studies using (45 colony bees in 5 main regions in various geographical and climatic zone environmental conditions. The obtained data were compared with the Apis mellifera carnica reference samples, Apis mellifera caucasica, and Apis mellifera mellifera. Morphometric identification was carried out using 19 landmarks by IdentiFly software. Almost all colonies showed belonging to the lineage C (about 85%), by subspecies to A. m. carnica, A. m. caucasica showed 11%, A. m. mellifera belonged to only 4%. Furthermore, using multivariate principal component analysis compared honeybee lineages between reference samples. There were significant differences in wing landmarks between lineages and subspecies (Mahalanobis square distance). By Mahalanobis, distances between the evolutionary lineages M differ from line C by 15.93 and from line O by 19.03 units. In contrast, the distance between lines C and O is insignificant, with satisfactory reliability. The forewing wing size evaluated centroid size, which showed the highest degree of honeybees in the west and south Kazakhstan zones. The percentage of variation in wing centroids was relatively small between analyzed samples (less than 1%) but extremely changed for reference samples A. m. carnica, A. m. caucasica, A. m. mellifera, where log centroid sizes showed 1.33%, 4.18%, and 4.67%, respectively. The results showed significant differences between populations in different climatic zones.